Enhancing Employee Performance Through Organization Culture, Workload, and Job Engagement - Putri, Inggit Fachtianna; Fitriani, Rizka Ayu; Hardjowikarto, Dharliana; Sunimah, (Journal Research of Social Science, Economics, and Management, 2025)
Employee performance in public sector agencies managing natural resources is critical for effective service delivery and societal well-being. However, the influence of workload, organizational culture, and job engagement on employee performance remains unclear, with mixed findings reported in previous studies. This study aims to analyze the individual and combined effects of these factors on employee performance at the Cimanuk-Cisanggarung Cirebon River Area Center. Employing a quantitative associative method, data were collected from 131 employees using census sampling and analyzed with multiple regression via SPSS 22. Results reveal that workload and organizational culture do not significantly affect employee performance individually, whereas job engagement significantly enhances performance. Nevertheless, collectively, workload, organizational culture, and job engagement have a significant positive effect, explaining 47.4% of the variance in employee performance. These findings suggest that while managing workload and fostering a supportive culture are important, enhancing employee engagement is pivotal for performance improvements. The study highlights the necessity of balanced workload distribution, cultivation of an aligned organizational culture, and fostering job engagement to optimize employee productivity. For practice, agencies should design integrated human resource strategies focusing on these areas to enhance organizational outcomes. Future research is recommended to explore additional variables such as leadership style and motivation using longitudinal designs to deepen understanding of employee performance dynamics.